Electronic Structures and Reactivity Profiles of Aryl Nitrenoid-Bridged Dicopper Complexes - Carsch, Kurtis M.; Lukens, James T.; DiMucci, Ida M.; Iovan, Diana A.; Zheng, Shao-Liang; Lancaster, Kyle M.; Betley, Theodore A. (Journal of the American Chemical Society, 2020)
Dicopper complexes templated by dinucleating, pacman dipyrrin ligand scaffolds ((Mes)dmx, (tBu)dmx: dimethylxanthine-bridged, cofacial bis-dipyrrin) were synthesized by deprotonation/metalation with mesitylcopper (CuMes; Mes: mesityl) or by transmetalation with cuprous precursors from the corresponding deprotonated ligand. Neutral imide complexes ((R)dmx)Cu-2(mu(2)-NAr) (R: Mes, Bu-t; Ar: 4-MeOC6H4, 3,5-(F3C),C6H3) were synthesized by treatment of the corresponding dicuprous complexes with aryl azides. While one-electron reduction of ((Mes)dmx)Cu-2(mu(2)-N(C6H4OMe)) with potassium graphite initiates an intramolecular, benzylic C-H amination at room temperature, chemical reduction of ((tBu)dmx)Cu-2(mu(2)-NAr) leads to isolable [((tBu)dmx)Cu-2(mu(2)-NAr)](-) product salts. The electronic structures of the thermally robust [((tBu)dmx)Cu-2(mu(2)-NAr)](0/-) complexes were assessed by variable-temperature electron paramagnetic resonance spectroscopy, X-ray absorption spectroscopy (Cu L-2,L-3/K-edge, N K-edge), optical spectroscopy, and DFT/CASSCF calculations. These data indicate that the formally Class IIIA mixed valence complexes of the type [((R)dmx)Cu-2(mu(2)-NAr)](-) feature significant NAr-localized spin following reduction from electronic population of the [Cu-2(mu(2)-NAr)] pi* manifold, contrasting previous methods for engendering iminyl character through chemical oxidation. The reactivity of the isolable imido and iminyl complexes are examined for prototypical radical-promoted reactivity (e.g., nitrene transfer and H-atom abstraction), where the divergent reactivity is rationalized by the relative degree of N-radical character afforded from different aryl substituents.